Adolescent attitudes, beliefs, and concerns regarding breastfeeding. - Nelson, Antonia M (MCN. The American journal of maternal child nursing, 2009)
Purpose: To investigate the attitudes, beliefs, and concerns of pregnant and postpartum adolescents regarding breastfeeding. Study Design and Methods: Audiotaped focus groups of low-income, largely minority pregnant and postpartum adolescents were conducted and transcripts analyzed using content analysis techniques. Findings: Major themes identified were in the area of beliefs, such as They say it's healthy, or It hurts; attitudes, such as breastfeeding is the mother's choice and The baby comes first; and concerns such as privacy, and Breastfeeding leads to dependency. Clinical Implications: Adolescents can be encouraged to breastfeed, but require appropriate education beyond what they have heard from others. Myths such as pain during breastfeeding need to be addressed. Since teens want to learn but not be told what to do, active learning strategies such as guided Internet searches could be helpful to guide them into discovery of the benefits of breastfeeding. Since all the teens in this study felt that the baby comes first, emphasizing the benefits of breastfeeding for the baby should predominate educational efforts. Concerns related to physical exposure while breastfeeding can be addressed antenatally through discussing creative strategies to maintain modesty. This study suggests that, in the postpartum hospital setting, adopting a sensitive, initially hands-off' approach to supporting breastfeeding might be more well-accepted than tactile assistance, and that following the initial establishment of a milk supply, various levels of breastfeeding exclusivity should be considered as potentially acceptable infant feeding patterns.
17 citations (Crossref) [2023-10-31] Place: United States Nelson, Antonia M. Southern Connecticut State University, New Haven, CT, USA. nelsona13@southernct.edu
Keywords: *Breast Feeding/px [Psychology]; *Health Knowledge; Attitudes; Practice; *Mothers/ed [Education]; *Mothers/px [Psychology]; *Psychology; Adolescent; Adolescent; Adolescent Psychology; Breast Feeding; Breastfeeding; Female; Focus Groups; Focus groups; Health Knowledge; Attitudes; Practice; Health Promotion; Humans; Mothers; Postpartum Period; Postpartum Period/px [Psychology]; Pregnancy; Qualitative research; Young Adult; adolescent; adult; article; attitude to health; breast feeding; child psychology; dept.nur; education; female; health promotion; human; information processing; mother; pregnancy; psychological aspect; puerperium